Optoelectronic photoinduced charge transfer system with mu 3PhN-Ru-3 cluster functionalized single-walled carbon nanotubes - Lee, Wonjoo; Koo, Gumae; Ogale, Satishchandra B.; Han, Sung-Hwan (Journal of Materials Chemistry C, 2009)
Optoelectronic photoinduced charges have been attracting great attention lately in view of their applicability to diverse optoelectronic device systems. Here, we report the design and implementation of a charge transfer system based on triruthenium (Ru) cluster compounds on viologen modified single-walled carbon nanotubes (V-SWNTs) by an in situ preparation method. We examine the photoinduced (intensity dependent and temporal) changes in the transport properties of the Ru-cluster functionalized V-SWNT coating and identify the possible charge transfer mechanism. Furthermore, we demonstrate the applicability of such Ru-cluster functionalized V-SWNT films to photoelectrochemical cells.